Current Neonatal Resuscitation Practices among Paediatricians in Gujarat, India - Satvik C. Bansal; Archana S. Nimbalkar; Dipen V. Patel; Ankur R. Sethi; Ajay G. Phatak; Somashekhar M. Nimbalkar (Hindawi Limited, 2014)
Aim. We assessed neonatal resuscitation practices among paediatricians in Gujarat. Methods. Cross-sectional survey of 23 questions based on guidelines of Neonatal Resuscitation Program (NRP) and Navjaat Shishu Suraksha Karyakram (NSSK) was conducted using web-based tool. Questionnaire was developed and consensually validated by three neonatologists. Results. Total of 142 (21.2%) of 669 paediatricians of Gujarat, India, whose e-mail addresses were available, attempted the survey and, from them, 126 were eligible. Of these, 74 (58.7%) were trained in neonatal resuscitation. Neonatal Intensive Care Unit with mechanical ventilation facilities was available for 54% of respondents. Eighty-eight (69.8%) reported correct knowledge and practice regarding effective bag and mask ventilation (BMV) and chest compressions. Knowledge and practice about continuous positive airway pressure use in delivery room were reported in 18.3% and 30.2% reported use of room air for BMV during resuscitation. Suctioning oral cavity before delivery in meconium stained liquor was reported by 27.8% and 38.1% cut the cord after a minute of birth. Paediatricians with NRP training used appropriate method of tracheal suction in cases of nonvigorous newborns than those who were not trained. Conclusions. Contemporary knowledge about neonatal resuscitative practices in paediatricians is lacking and requires improvement. Web-based tools provided low response in this survey.